Energy–poverty–inequality SDGs: A large-scale household analysis and forecasting in China - Cong Li; Minglai Li; Lin Zhang; Qiang Li; Hua Zheng; Marcus W. Feldman (Proceedings of the National Academy of Sciences, 2025)
Affordable and clean energy, eliminating poverty, and reducing inequality are important goals of the United Nations Sustainable Development Goals (SDGs). This paper examines the role of access to clean cooking fuels in promoting income growth and reducing income inequality. Using data from Chinese households, we show that a 10% increase in the adoption of clean cooking fuels would result in an increase in total annual household income of US$37 billion nationwide. Income growth from access to clean cooking fuels is greater for lower-income groups due to a shift to higher household income and reduced downward household income mobility, which contributes to a reduction in income inequality. The effect of access to clean cooking fuels on household income growth is primarily driven by improved health and increased labor supply. The use of clean cooking fuels also saves fuel collection time and cooking time, reducing time spent on household chores by about 0.4 h per day, thereby increasing labor supply in the job market and improving wage income. Improvements in income due to clean cooking fuels are influenced by external conditions, urbanization, education, employment opportunities, and good market conditions. With further promotion of clean cooking fuels, household income and inequality in China are expected to improve further by 2030 and contribute more widely to human well-being and achievement of the SDGs.